Public Relations in Librarianship and Mass Media - Erol Yılmaz (Türk Kütüphaneciliği)
Public relations is an indispensable management function for an organization to reach its target audiences so as to serve them better and, at the same time, to upgrade its status in society as an organization. This ıvas noticed a long time ago in developed countries in the field of librarianship as well as in other fields and the ıvork has been started accordingly. İn this study to examine to see if radio, television and nevospa- pers, which are effective tools in public relations practices, are used in Turkish librarianship. Data was gathered through a questionnaire vohich ıvas complated by 59 li- braries of various types. İt ıvas discovered that public relations is not utilized in a planned manner in the field of librarianship in Turkey, and radio, television and nevospapers are not made use of for this purpose.